2019
DOI: 10.1016/j.jnutbio.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the mouse white adipose tissue redox environment and associations with perinatal environmental exposures to bisphenol A and high-fat diets

Abstract: White adipose tissue (WAT) plays an important role in obesity pathophysiology. Redox signaling underlies several aspects of WAT physiology; however, the thiol redox environment of WAT has not yet been fully characterized. Dietary and endocrine disrupting chemical (EDC) exposures during development can transiently impact the cellular redox environment, but it is unknown whether these exposures can reprogram the WAT thiol redox environment. To characterize the WAT thiol redox environment, we took a descriptive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…Our results showed that BPA intoxication increased the body weight of the experimental rats Neier et al (2019). reported a gradual increase in body weight in the offspring of 12-27-weeks -old C57BL/6J female mice that were fed on Chow diet Gestation day 9 to PND 21 at a dose of 50 μg/kg/ day.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…Our results showed that BPA intoxication increased the body weight of the experimental rats Neier et al (2019). reported a gradual increase in body weight in the offspring of 12-27-weeks -old C57BL/6J female mice that were fed on Chow diet Gestation day 9 to PND 21 at a dose of 50 μg/kg/ day.…”
supporting
confidence: 50%
“…Our results showed that BPA intoxication increased the body weight of the experimental rats. Neier et al ( 2019 ) reported a gradual increase in body weight in the offspring of 12–27‐weeks ‐old C57BL/6J female mice that were fed on Chow diet Gestation day 9 to PND 21 at a dose of 50 μg/kg/day. According to Tian et al ( 2021 ) reported that exposure to BPA and tetrabromobisphenol A at 20, 100, and 500 μg/L/day elevated the body weight, length, and food intake in male zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…In part, these changes are associated with enhanced adipocyte size, infiltration of inflammatory leukocytes, and elevated expression of lipogenic markers, like PPAR-γ and SREBP [ 113 ]. Developmental exposure to BPA has also been linked to enhanced levels of oxidative stress in the adipose of exposed offspring however, such an effect was not prevented by exposure to a perinatal Mediterranean diet that is known to offer protection against oxidative stress [ 114 ]. There may also be a greater number of adipocytes in the BAT of adult mouse offspring exposed to phalate during gestational and lactational development [ 111 ].…”
Section: Adipose Tissuesmentioning
confidence: 99%
“…To resemble human exposure conditions, the daily treatment or the vehicle was given orally to the dams by means of a pipette to minimize the dams’ stress (Bo et al 2016 ; Palanza et al 2002 ). This type of administration allowed us to perform a perinatal treatment (covering both prenatal and postnatal critical windows of development) (Neier et al 2019 ) on the offspring. In fact, it is known that both BPA and BPS can pass first through the placenta and then into the milk during lactation (Cimmino et al 2020 ; Mao et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%